A területfejlesztés irányításának kérdései - Illés, Iván (Tér és Társadalom, 1992)
At present, regional development is facing far more difficult, complicated and urgent problems than any time before during the lant 50 years. In the first place, it is the consequence of new, objective economic conditions: Overall and extensive economic recession exerts its influence in a regionally differentiated way. It is unavoidable, that new economic units, which have no solid foundations, and are integrated into the local economy, are the first victims of economic crisis, especially when their future is decided at far-away headquarters; Re-orientation of foreign trade and the collapse of Eastern markets primarily jeopardize the Eastern parts of the country which had been oriented to these regions. At the same time, Western operating capital, commission work and cooperation understandably favour and promote the development of the Western parts of the country. The separation of the country on the basis of economic development is clearly and excessively becoming a characteristic feature; With the market economy gaining ground the market factors, are gaining importance, and with the increasing differentiation of the economic factors the differences in allowances and taxes are becoming increasingly characteristic, and they all add to the increase of differences. In effect, the differentiating factors of the market only start to exert their influence in regional sense and terms. but their final influence and consequences are unknown as yet; Finally, new and yet incomprehensible systems of dependencies begin to develop. Hungarian and foreign companies buy up other companies or get a majority share in them, sometimes for the purpose of development, and sometimes for other reasons. Parallel with it, all those systems and structures that were created for safeguarding the interests at certain regional levels have disappeared (the state party with its regional organization, the county councils, etc. have all ceased to exist). The logical consequence stemming from this is that in the transitional period, a strong function and management for regional development has to be created within the government. At present in Hungary the prevailance of a well-determined governmental regional development policy containing the elements of redistribution, but not being limited to the fundamental system of the infrastructure, is absolutely necessary. Consequently, the government has to be given a special role. As opposed to this, the actual practise of government regional development policy is inconsistent, slow and unplanned. The basic directions, fundamental principles and the concept of government regional development policy have not been elaborated as yet. Measures on regional development are ad hoc, and of fire-fighting character. The functions of regional and settlement development are still fulfilled by different portfolios and have no clear distribution of tasks. As a consequence, the most urgent thing to do is to determine the obligations, duties, tasks and spheres of influence of the government in regional development. As a first step, a clear and well-defined regional development programme – with or without legislation – has to be elaborated. Regional development requires strong and uniform representation by the government. And last, but not least, the political, economic and social problems of the representation of interests at regional level should be solved. One of the solutions could be a parliament with two houses, where the representatives of one of the houses would represent regions, counties, etc. The other solution could be the system of strong and representative regional local governments.